Correction: In situ plasma-assisted atmospheric nitrogen fixation using water and spray-type jet plasma. Issue 89 (25th October 2018) - Peng, Peng; Chen, Paul; Addy, Min; Cheng, Yanling; Zhang, Yaning; Anderson, Erik; Zhou, Nan; Schiappacasse, Charles; Hatzenbeller, Raymond; Fan, Liangliang; Liu, Shiyu; Chen, Dongjie; et al.
Abstract : Correction for ' In situ plasma-assisted atmospheric nitrogen fixation using water and spray-type jet plasma' by Peng Peng et al., Chem. Commun., 2018, 54, 2886–2889.